Anaerobic metabolism characteristics of female boxers in different competitive levels - Ma, Y.; Li, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this study is to discuss characteristics of the anaerobic metabolism of female boxers in different levels of competition.